Is Anti-IL 5 Therapy Effective in Eosinophilic Granulomatosis With Polyangiitis?. Issue 6 (November 2017) - Krishna, Rachana; West, Frances M.; Zappetti, Dana
Abstract : Synopsis: In patients with EGPA who are glucocorticoid dependent, use of mepolizumab decreased the use of glucocorticoids and increased rates of remission compared with placebo. Source: Wechsler ME, Akuthota P, Jayne D, et al. Mepolizumab or placebo for eosinophilic granulomatosis with polyangiitis. N Engl J Med 2017; 376:1921–932.